Supervised Curricular Internship II: Experiences of the future chemistry teacher in remote education (Research, Society and Development, 2021)
The research analyzed the experiences of 20 (twenty) students developed in Remote Teaching (ER) in the 1st semester of 2021 after completing the Supervised Curricular Internship II. A qualitative and quantitative approach was carried out using a virtual questionnaire created on the Google Forms® digital platform, to investigate the choice of the Chemistry Degree course, conditions of access to digital technologies, pedagogical tools used during the internship, adversities encountered by these students during the realization of the internship and the contributions of the remote internship for the formation of the Graduate in Chemistry. After analyzing and tabulating the data, the research presented the following results: the students chose a degree because they like to teach and because of their insertion in the job market, they accessed digital technologies at home, using smartphones through a broadband service with good quality connection, used Google Meet®, WhatsApp® and VLE virtual learning environment as pedagogical tools during the internship. Internet access, lack of knowledge in digital media and adaptation to remote classes were the adversities encountered during the internship. Learning and using different technological resources and digital platforms were the main contributions of the internship to the formation of decent people. The virtual remote internship enabled and provided opportunities for varied everyday experiences, promoting reflection on teaching work.